(untitled) (Global Journal of Science Frontier Research, 2018)
It was already said, that Maxwell’s equations do not include information about power interaction of the current carrying systems. In the classical electrodynamics for calculating such an interaction it is necessary to calculate magnetic field in the assigned region of space, and then, using a Lorentz force, to find the forces, which act on the moving charges. Obscure a question about that remains with this approach, to what are applied the reacting forces with respect to those forces, which act on the moving charges. It is experimentally discovered, that when along the conductor flows the current, it loses electro neutrality and finds around itself radial static electric field; however, classical electrodynamics cannot explain this fact. In the article are given the experimental data, which attest to the fact that around the superconductive windings and the tori, into which is introduced direct current, is formed static electric field. This fact finds its explanation within the framework the concept of scalar-vector potential.